1998
DOI: 10.1073/pnas.95.3.1131
|View full text |Cite
|
Sign up to set email alerts
|

p21 WAF-1 reorganizes the nucleus in tumor suppression

Abstract: Interphasic nuclear organization has a key function in genome biology. We demonstrate that p21 WAF-1 , by inf luencing gene expression and inducing chromosomal repositioning in tumor suppression, plays a major role as a nuclear organizer. Transfection of U937 tumor cells with p21 WAF-1 resulted in expression of the HUMSIAH (human seven in absentia homologue), Rb, and Rbr-2 genes and strong suppression of the malignant phenotype. p21 WAF-1 drastically modified the compartmentalization of the nuclear genome. DNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…Impairing endogenous NuMA during or upon acinar differentiation using NuMA-CT peptide or antiNuMA-CT antibodies modifies the distribution of the chromatin markers acetyl-H4 and H4K20m. Changes in higher order chromatin organization are confirmed by the alteration of the distribution of DNase I sensitive regions, indicative of modifications in genome exposure (Linares-Cruz et al, 1998). The induced alteration of H4K20m and acetyl-H4 distribution by NuMA antibodies, which occurs before the loss of acinar differentiation, suggests a direct effect of NuMA on chromatin organization.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Impairing endogenous NuMA during or upon acinar differentiation using NuMA-CT peptide or antiNuMA-CT antibodies modifies the distribution of the chromatin markers acetyl-H4 and H4K20m. Changes in higher order chromatin organization are confirmed by the alteration of the distribution of DNase I sensitive regions, indicative of modifications in genome exposure (Linares-Cruz et al, 1998). The induced alteration of H4K20m and acetyl-H4 distribution by NuMA antibodies, which occurs before the loss of acinar differentiation, suggests a direct effect of NuMA on chromatin organization.…”
Section: Discussionmentioning
confidence: 76%
“…Using this technique it has been shown that DNase I-sensitive chromatin densely locates to the periphery of the cell nucleus in differentiated and reverse-transformed cells but not in transformed cells (Krystosek and Puck, 1990;Linares-Cruz et al, 1998). In situ nick translation revealed that 83% of NuMA 2002-2101 -S1, 68.7% of insertless vector-S1, and 89.6% of control S1 acinar cells had a marked nuclear peripheral location of DNase I-sensitive chromatin.…”
Section: Peptide-and Antibody-induced Alteration Of Numa Distributionmentioning
confidence: 99%
“…Multinucleated and giant cells were also observed following p21 Waf-1 transfection of MCF-7 cells (Sheikh et al, 1995). Previously we showed that SIAH-1 transcription was increased following p21 Waf-1 transfection in U937 leukemia cells (Linares-Cruz et al, 1998) without evident mitotic abnormalities. On the other hand reduced p21 Waf-1 expression also resulted in gross nuclear abnormalities and centriole overduplication (Mantel et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…Expression of SIAH-1 was also induced following transfection of p21 Waf-1 , a cyclin-dependent kinase inhibitor, along with spatial nuclear reorganization and tumor suppression (Linares-Cruz et al, 1998). To investigate the functional role of SIAH-1, the SIAH-1-cDNA coding sequence was transfected into the MCF7 human breast cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…A series of reports have suggested an alternative approach, namely, to analyze what it is that causes a malignant cell to revert. [7][8][9][10][11][12] It is postulated that the molecular mechanisms for overriding cancer are present in such revertant cells and that it is possible to determine the key factors that reverse malignancy which are selected for in cancer cells. 11,12 An understanding of how this reversion happens may lead to the identification of targets that were not previously revealed by comparing normal and tumor cells.…”
Section: Introductionmentioning
confidence: 99%